Measuring and optimizing the urban community resilience against public health emergencies: a case study in Nanjing, China - Cui, Peng; Cao, Saiya; Qin, Ruize; Zhang, Fan; Li, Dezhi; Feng, Lan (Frontiers in Public Health, 2025)
IntroductionUrban communities, as the basic unit of urban governance, play a crucial role in responding to public health emergencies (PHEs). This study aims to investigate the resilience measurement and optimization strategies of urban communities in responding to PHEs in order to improve their resilience.MethodsThe study constructed a resilience assessment framework and identified 31 key influencing factors to measure the resilience of case communities in Nanjing. Through sensitivity analysis, static optimization strategies were proposed from social, environmental, and economic levels. Dynamic Bayesian network inference simulation and importance analysis were used to propose dynamic optimization strategies from pre, during, and long-term perspectives.ResultsThrough the combination of dynamic and static strategies, community managers promote resilience building from both short-term and long-term perspectives.DiscussionThe study provides a valuable reference for comprehensively improving the emergency management system.